Haplotype analysis of the NADPH oxidase p22 phox gene in patients with bronchial asthma - Izakovicova Holla, Lydie; Kanková, Katerina; Znojil, Vladimir (International archives of allergy and immunology, 2009)
BACKGROUND: Superoxide produced by airway epithelial and inflammatory cells may contribute to the pathogenesis of asthma. NADPH oxidase (an enzyme complex made up of 5 subunits) is a major source of superoxide in cells. We sought to elucidate the role of genetic variability in the gene encoding the p22(phox) subunit of the NADPH oxidase (CYBA, 16q24.3) in asthma susceptibility by means of an association study of haplotypes based on 3 common single nucleotide polymorphisms (SNPs), -930A/G, 242C/T (H72Y) and 640A/G. METHODS: SNPs were genotyped by PCR-RFLP methods in a cohort of age- and sex-matched subjects with bronchial asthma (n = 305) and healthy controls (n = 311). Haplotypes were constructed in silico using a Monte Carlo-based algorithm. Furthermore, association of SNPs with sensitization to selected allergens (total 15 tested by skin prick test positivity/negativity) was analyzed. RESULTS: In a single locus analysis, SNPs 242C/T and 640A/G were marginally significantly associated with asthma (p = 0.036 and 0.036, respectively). SNP 640A/G showed a significant association with sensitization to 2 allergens tested (p(corr) < 0.02). Haplotype analysis identified a total of 8 haplotypes with population frequencies from 0.07 to 0.22. Distribution of haplotypes significantly differed between cases and controls (omnibus p = 0.017, 10,000 permutations). In the post-hoc analysis, haplotype CYBA(3) (-930G/242T/640A) was associated with an increased risk of asthma (p(corr) < 0.05; OR = 1.43, 95% CI 1.06-1.93). CONCLUSIONS: This study supports the hypothesis that genetic variability in the CYBA gene probably contributes to the susceptibility to bronchial asthma (or its related phenotypes) in our population.
Keywords: Skin Tests; bronchiální astma; kožní testy; mužské pohlaví; genetická predispozice k nemoci; Male; Allergens; Gene Frequency; Female; Humans; NADPH-oxidasy; Haplotypes; Genetic Predisposition to Disease; Polymorphism, Single Nucleotide; lidé; Middle Aged; ženské pohlaví; lidé středního věku; jednonukleotidový polymorfismus; studie případů a kontrol; Case-Control Studies; NADPH Oxidases; frekvence genu; alergeny; dospělí; Adult; haplotypy; Asthma